Electroporation-Mediated Gene Delivery of Na+, K+-ATPase, and ENaC Subunits to the Lung Attenuates Acute Respiratory Distress Syndrome in a Two-Hit Porcine Model. Issue 1 (January 2015) - Emr, Bryanna M.; Roy, Shreyas; Kollisch-Singule, Michaela; Gatto, Louis A.; Barravecchia, Michael; Lin, Xin; Young, Jennifer L.; Wang, Guirong; Liu, Jiao; Satalin, Joshua; Snyder, Kathleen; Nieman, Gary F.; et al.
Abstract : ABSTRACT: Introduction : Acute respiratory distress syndrome (ARDS) is a common cause of organ failure with an associated mortality rate of 40%. The initiating event is disruption of alveolar-capillary interface causing leakage of edema into alveoli.Hypothesis : Electroporation-mediated gene delivery of epithelial sodium channel (ENaC) and Na +, K + -ATPase into alveolar cells would improve alveolar clearance of edema and attenuate ARDS.Methods : Pigs were anesthetized and instrumented, and the superior mesenteric artery was clamped to cause gut ischemia/reperfusion injury and peritoneal sepsis by fecal clot implantation. Animals were ventilated according to ARDSnet protocol. Four hours after injury, animals were randomized into groups: (i) treatment: Na +, K + -ATPase/ENaC plasmid (n = 5) and (ii) control: empty plasmid (n = 5). Plasmids were delivered to the lung using bronchoscope. Electroporation was delivered using eight-square-wave electric pulses across the chest. Following electroporation, pigs were monitored 48 h.Results : The Pao2 /Fio2 ratio and lung compliance were higher in the treatment group. Lung wet/dry ratio was lower in the treatment group. Relative expression of the Na +, K + -ATPase transgene was higher throughout lungs receiving treatment plasmids. Quantitative histopathology revealed a reduction in intra-alveolar fibrin in the treatment group. Bronchoalveolar lavage showed increased surfactant protein B in the treatment group. Survival was improved in the treatment group.Conclusions : Electroporation-mediated transfer of Na +, K + -ATPase/ENaC plasmids improved lung function, reduced fibrin deposits, decreased lung edema, and improved survival in a translational porcine model of ARDS. Gene therapy can attenuate ARDS pathophysiology in a high-fidelity animal model, suggesting a potential new therapy for patients.